Abdominal radical trachelectomy in fertility-sparing treatment of early-stage cervical cancer - Cibula, David; Sláma, Jiří; Svárovský, Jiří; Fischerová, Daniela; Freitag, Pavel; Zikán, Michal; Pinkavová, Ivana; Pavlišta, David; Dundr, Pavel; Hill, Martin (International journal of gynecological cancer, 2009)
BACKGROUND: Abdominal radical trachelectomy (ART) is one of the fertility-sparing procedures in women with early-stage cervical cancer. In comparison with vaginal radical trachelectomy, the published results of ART are so far limited. METHODS: Enrolled were women referred for ART either by laparoscopy or laparotomy. The main inclusion criterion was stage IA2 or IB1 with a cranial extent that allows for preservation of at least 1 cm of the endocervical canal. RESULTS: A total of 24 women were referred for the procedure, but fertility could not be preserved in 7 (29%) of them. Four women underwent immediate completion of radical hysterectomy because of a positive cranial surgical margin (n = 2) or sentinel node macrometastasis (n = 2) on frozen section. We found no correlation between tumor volume and inability to preserve fertility. A positive sentinel node was identified in 4 patients (17%); there were no false-negative results. Of the 9 women (53%) who have tried to conceive so far, 6 (67%) have conceived and 5 given birth, 2 of which were premature deliveries. CONCLUSIONS: Fertility cannot be preserved because of positive cranial margins or involved lymph nodes in almost one third of patients originally referred for radical trachelectomy. The main criterion for the selection of suitable patients should be the cranial extent of the tumor. Abdominal radical trachelectomy allows for achievement of satisfactory obstetrical outcomes.
Keywords: dospělí; gynekologické chirurgické výkony; Carcinoma, Squamous Cell; Female; Lymphatic Metastasis; lymfatické metastázy; Adult; výsledek terapie; ženské pohlaví; břicho; lidé; fertilita; staging nádorů; Treatment Outcome; následné studie; nádory děložního čípku; prognóza; Humans; biopsie sentinelové lymfatické uzliny; Fertility; Adenocarcinoma; Follow-Up Studies; spinocelulární karcinom; adenokarcinom; hysterektomie; Prognosis; Sentinel Lymph Node Biopsy; Gynecologic Surgical Procedures; Uterine Cervical Neoplasms; Neoplasm Staging; Hysterectomy; Abdomen